Effect of Solution Treatment on the Age-Hardening Behavior of Al-12Si-1Mg-1Cu Piston Alloy with Trace-Zr Addition - Kaiser, Mohammad Salim (Journal of Casting & Materials Engineering, 2018)
The influence of a solution treatment with a trace zirconium addition on the precipitation behavior of a cast Al-12%Si-1%Mg-1%Cu piston alloy has been reported. The alloys were prepared by controlled melting and casting. The cast alloys were given an age-hardening treatment having a sequence of homogenization, T6 solutionizing, quenching, and aging. Both the cast and solutionized samples were naturally aged for 58 days, isochronally aged for 60 minutes at different temperatures (up to 350°C), and isothermally aged at various temperatures (up to 225°C) for different periods of time (ranging from 15 to 360 minutes). The hardness values of the differently processed alloys were measured to understand the aging behavior of the alloys. Electrical resistivity changes with aging time and temperature were measured to understand the precipitation behavior of the alloys. It is observed that significant hardening takes place in the aged alloys due to the formation of GP zones as well as the formation of metastable phases. The solutionizing treatment improves the hardness because some alloying elements are re-dissolved during solution treatment to produce a solute-rich solid solution. The trace-added Zr hinders the softening due to the precipitation of Al3Zr, which is very stable against coarsening and the re-dissolution of precipitates. Electrical resistivity decreases due to stress relieving, the dissolution of the metastable phase, and precipitation coarsening. The resistivity of the solutionized alloys decreases more due to the higher concentration of elements in the solid solution. A microstructural study of the alloys reveals that the solution treatment improves the distribution of the silicon grains. It is also observed that the alloys attained an almost fully re-crystallized state after aging at 350°C for 90 minutes.